Postgraduate education and training in drug development sciences: 30 years of the european center of pharmaceutical medicine - Annette Mollet; Nastazja Laskowski; Thomas Szucs (Frontiers Media S.A., 2024)
The European Center of Pharmaceutical Medicine (ECPM), affiliated with the University of Basel Department of Public Health, stands as a leading institution dedicated to advancing education in medicine development since 1991. At the heart of its educational offers lies the Diploma or Certificate (DAS or CAS) in Pharmaceutical Medicine, encompassing a comprehensive curriculum that covers the entire drug development process. ECPM has expanded its reach beyond Switzerland, offering courses in the USA, China and India. Through rigorous teaching and strategic alliances, ECPM continues to shape education in pharmaceutical medicine on an international scale.